STUDI KARAKTERISTIK MOMEN TORSI AKUMULATOR PEGAS UNTUK PENGGERAK LANGKAH (STEP-DRIVES) - Danny S Pelupessy (ALE Proceeding, 2019)
Abstrak This paper considers and analyzes the torque characteristics of spring accumulators with output rotary link, designed for stepper drives, reciprocating movements and in balancing systems, provides recommendations for their use. General idea of realization of the principle of recuperation with accumulation of potential energy of the deformed springs in this work consists in use of spring accumulators with cylindrical springs of tension or compression.